The study of CO2 reforming of methane over Ce/Sm-promoted NiCaAl catalysts - Taherian, Zahra; Gharahshiran, Vahid Shahed; Orooji, Yasin; Karimi-Maleh, Hassan; Khataee, Alireza (Elsevier, 2023)
In this work, we synthesized Ce and Sm-promoted NiCaAl layered catalysts via co-precipitation and freeze-drying strategies for alleviating some problems, such as coke deposition and agglomeration of active sites, in dry reforming of methane. Employing such promoters leads to rising O2 vacancies on the catalyst's surface, resulting from adsorbing CO2 gas under the reaction. X-ray diffraction (XRD) analysis confirmed the formation of a hydrotalcite network. High-resolution transmission electron microscopy (HR-TEM) and field emission scanning electron microscopy (FE-SEM) images also indicated a wealth of nanocatalysts, well distributed on the surface and within a porous scaffold structure. The temperature-programmed reduction (H2-TPR) proved that cerium (H2 consumption = 1.2 mmol.g-1) could weaken the interactions between nickel and Ca/Al, leading to better reducibility than samarium (H2 consumption = 1.35 mmol.g-1). Moreover, the temperature-programmed deposition (CO2-TPD) showed the Ce-promoted catalyst possesses more basic sites (0.41 mmol.g-1) on its sur-face than the Sm-enhanced one (0.25 mmol.g-1). Consequently, the Ce-enhanced catalyst with a smaller crys-tallite size (8.9 nm), higher dispersion of Ni (10.8%), better reducibility, and more basic sites, which caused the highest methane conversion (82%), and H2/CO ratio (0.9) at 700 degrees C without any coke deposition after 5 h of time on stream.
Keywords: NiCaAl; Hydrotalcite; Methane dry reforming; Cerium; Samarium